Toxicological and Mutagenic Effects of Particulate Matter from Domestic Activities - Daniela Figueiredo; Estela D. Vicente; Ana Vicente; Cátia Gonçalves; Isabel Lopes; Célia A. Alves; Helena Oliveira (Toxics, 2023)
People spend most of their time indoors, particularly in their houses where daily activities are carried out, enhancing particulate matter (PM) emissions with consequent adverse health impacts. This study intended to appraise the toxicological and mutagenic responses of particulate matter with a diameter less than 10 μm (PM10) released from cooking and ironing activities under different conditions. The cytotoxicity of the PM10 total organic extracts was tested in A549 cells using the WST-8 and the lactate dehydrogenase (LDH) assays, while the interference in cell cycle dynamics and reactive oxygen species (ROS) production was analysed by flow cytometry. The S. typhimurium TA98 and TA100 Ames tester strains with and without metabolic activation were employed to determine the mutagenic potential of the PM10-bound polycyclic aromatic hydrocarbons (PAHs). PM10 organic extracts decreased the metabolic activity of A549 cells; however, no effects in the LDH release were observed. An increase in ROS levels was registered only for cells treated with PM10 at IC20 from steam ironing, in low ventilation conditions, while cell cycle dynamics was only affected by exposure to PM10 at IC20 from frying horse mackerel and grilling boneless pork strips. No mutagenic effects were observed for all the PM10-bound PAHs samples.